Barriers to occupational health and safety management in small Brazilian enterprises - Garnica, Guilherme Besse; Barriga, Gladys Dorotea Cacsire (Associação Brasileira de Engenharia de Produção, 2018)
AbstractPaper aims To determine main barriers to the implementation of occupational health and safety management systems OHSMS in the context of small Brazilian enterprises from the perspectives of owners/managers, labor auditors, and OHS consultants.Originality: Survey with three different perspectives on small Brazilian enterprises.Research method: Survey conducted with stakeholders who influence the safety culture in small enterprises to identify the main barriers to the implementation of OHSMS.Main findings: Owners/managers tend to blame employees and the government for difficulty in implementing OHSMS, and external actors tend to blame management and resource allocation. Opinions converge on inappropriate management behavior, ineffective information and communication and production prioritization.Implications for theory and practice: These barriers should be overcome not only to facilitate the implementation of OHSMS but also to improve the conditions for the management of all small business operations.
Keywords: Work accident; Small business; Occupational Safety